All‐Carbon Pressure Sensors with High Performance and Excellent Chemical Resistance. Issue 13 (3rd March 2019) - Xiao, Zhuojian; Zhou, Weiya; Zhang, Nan; Zhang, Qiang; Xia, Xiaogang; Gu, Xiaogang; Wang, Yanchun; Xie, Sishen
Abstract: An all‐carbon pressure sensor is designed and fabricated based on reduced graphene oxide (rGO) nanomaterials. By sandwiching one layer of superelastic rGO aerogel between two freestanding high‐conductive rGO thin papers, the sensor works based on the contact resistance at the aerogel–paper interfaces, getting rid of the alien materials such as polymers and metals adopted in traditional sensors. Without the limitation of alien materials, the all‐carbon sensors demonstrate an ultrawide detecting range (0.72 Pa–130 kPa), low energy consumption (≈0.58 µW), ultrahigh sensitivity (349–253 kPa −1 ) at low‐pressure regime (<1.4 Pa), fast response time (8 ms at 1 kPa), high stability (10 000 unloading–loading cycles between 0 and 1 kPa), light weight (<10 mg), easily scalable fabrication process, and excellent chemical stability. These merits enable them to detect real‐time human physiological signals and monitor the weights of various droplets of not only water but also hazardous chemical reagents including strong acid, strong alkali, and organic solvents. This shows their great potential applications in real‐time health monitoring, sport performance detecting, harsh environment‐related robotics and industry, and so forth. Abstract : An all‐carbon pressure sensor, with light weight (<10 mg), high performance, and high chemical stability, is designed by combining freestanding superelastic reduced graphene oxide (rGO) aerogel and highly conductive rGO paper. It displays application in monitoring real‐time human physiological signals and weighting droplets of commonly used liquid or even hazardous chemical reagents.